Assessing the impacts of vehicle emissions and safety regulations - Bert van Wee (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2019)
This paper discusses how regulations can determine environmental and safety outcomes in transport systems. It explores the relationships between regulations and direct and indirect costs, and between regulations and benefits. It also discusses the ethical issues, such as the fact that cost-benefit analysis evaluates welfare effects but tends to ignore equity issues.
Keywords: 330